2021
DOI: 10.1007/s40620-020-00960-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying prognostic risk factors for poor outcome following COVID-19 disease among in-centre haemodialysis patients: role of inflammation and frailty

Abstract: Introduction The pandemic of coronavirus disease (COVID-19) has highly affected patients with comorbidities and frailty who cannot self-isolate, such as individuals undergoing haemodialysis. The aim of the study was to identify risk factors for mortality and hospitalisation, which may be useful in future disease spikes. Methods We collected data retrospectively from the electronic medical records of all patients receiving a diagnosis of COVID-19 between 11th March and 10th May 2020 undergoing maintenance haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 29 publications
8
35
0
2
Order By: Relevance
“…The most common health outcome reported was mortality (37 studies; 71.2%) 8,19,23,24,26,27,29,31–37,40–45,47–52,54–57,59,62–65,68,69 . The pooled odds ratio (OR) for unadjusted data associating frailty based on the CFS with mortality was 2.02 (95% confidence interval [CI] 1.62–2.51; I 2 83%; Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The most common health outcome reported was mortality (37 studies; 71.2%) 8,19,23,24,26,27,29,31–37,40–45,47–52,54–57,59,62–65,68,69 . The pooled odds ratio (OR) for unadjusted data associating frailty based on the CFS with mortality was 2.02 (95% confidence interval [CI] 1.62–2.51; I 2 83%; Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…In research articles reporting clinical manifestation and outcome of COVID-19 patients (78[54.4%]) the diagnosis of SARS-CoV-2 infection relied principally on RT-PCR (52[63.4%]) [ 11 20 , 32 , 61 , 62 , 69 , 93 , 94 , 100 , 108 111 , 113 , 115 124 , 126 , 129 , 132 , 134 , 135 , 138 151 ], serology (4[6.3%]) [ 18 , 20 , 22 24 , 86 , 99 ], RT-PCR and serological assay (5[6.6%])[ 29 31 , 85 , 127 , 152 ] or a combination of diagnostic tests including clinical evaluation [ 6 , 13 , 19 , 21 , 112 , 114 , 125 , 128 , 130 , 131 , 133 , 136 , 137 , 153 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
“…All outcome measures were influenced by the sample size, the age of patients, length of follow-up and policy of healthcare delivery. Excluding studies reporting outcome of patient admitted to hospital as a preventive measure and regardless of symptoms, we found that hospitalization of HD patients varied from 35 to 88.2% [ 11 13 , 17 , 21 , 32 , 62 , 82 , 93 , 109 , 114 , 116 , 118 , 120 , 127 , 129 , 133 , 136 138 , 144 , 145 , 150 , 154 ]. with a percentage of patients requiring ICU admission of 2.6–70.5% [ 6 , 13 , 17 , 21 , 32 , 62 , 109 , 114 , 116 , 118 , 119 , 121 , 125 , 126 , 129 – 134 , 136 , 138 , 143 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hendra et al in their study assessed HD patients with the mortality rate after testing positive for the novel SARS-CoV-2 by RT-PCR and identified prognostic risk factors associated with poor outcome including age, frailty and markers of inflammation [17].…”
Section: Discussionmentioning
confidence: 99%